2011
DOI: 10.1080/00087114.2011.10589766
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Rationale for Probable Amphidiploid Origin ofDipcadi erythraeumWebb. & Berth. - A Rare and Endemic Plant of Indian Thar Desert

Abstract: -Five accessions of Dipcadi erythraeum, a rare and endemic, bulbous medicinal plant of Thar desert in India, were collected from different districts of Rajasthan (India) to study the intra-specifi c genetic variation existing in their natural populations. To resolve species specifi c cytogenetical mechanism leading to evolution of D . erythraeum, mitotic and meiotic analyses were carried out. The karyotypes of various accessions of D. erythraeum were precisely resolved into ten distinct homologous pairs, not i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…In this study, we reconfirm 2n = 20 for D. montanum. Jakhi et al [31] first reported 2n = 22 and n = 11 in D. erythraeum collected from Rajasthan, reconfirmed by Jehan et al [12], although 2n = 20 has also been reported in the species [30]. We confirm 2n = 22 in D. erythraeum in two populations from Rajasthan.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…In this study, we reconfirm 2n = 20 for D. montanum. Jakhi et al [31] first reported 2n = 22 and n = 11 in D. erythraeum collected from Rajasthan, reconfirmed by Jehan et al [12], although 2n = 20 has also been reported in the species [30]. We confirm 2n = 22 in D. erythraeum in two populations from Rajasthan.…”
Section: Discussionsupporting
confidence: 85%
“…Somatic chromosome counts available globally for about 14 species of Dipcadi [25] have revealed wide diversity in chromosome number (2n = 6, 8, 16, 20, 22, 24, 32, 40). Since D. serotinum, with a broad distribution (Europe and Northern Africa to the Arabian Peninsula and India) shows 2n = 2x = 8 chromosomes with n = 4 [33], a base chromosome number [49,52] of x = 4 has been suggested [30]. Thus, considering x = 4, taxa with 2n = 12, 20, 22 in the present study may be polyploid derivatives.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Such information through association analysis of bivalents were reported in an important medicinally important desert plant i.e. Dipcadi erythraeum recently, which is also an amphidiploids ori-gin as revealed by cytogenetical investigation recently [18]. However, in the absence of karyological data it is difficult to confirm the apparent amphidiploids origin of the species.…”
Section: Resultsmentioning
confidence: 99%